The Conceptual and Mathematical Difficulties in Solving Reaction Rate Problems: A Diagnostic Study of Grade XI Students - Fajriani, Nur; Rudi, La; Esnawi, Esnawi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to analyze students’ conceptual and mathematical difficulties in solving chemistry problems on the topic of reaction rates. The research employed a descriptive quantitative approach with 27 eleventh-grade science students from SMA Negeri 12 Kendari as the subjects. The research instrument was a written diagnostic test designed to identify students’ conceptual and mathematical difficulties based on learning indicators for reaction rates. The data were analyzed by calculating the percentage levels of students’ difficulties for each indicator as well as the average difficulty for each aspect. The results show that, in the conceptual aspect, students’ difficulties fall into the moderate category with an average percentage of 46%, with the highest difficulty found in the indicator of relating changes in concentration to time (55%). In the mathematical aspect, students’ difficulties range from moderate to high, with an average percentage of 52%, where the highest difficulty occurs in the indicator of applying reaction rate formulas (65%). These findings indicate that students’ mathematical difficulties tend to be more dominant than their conceptual difficulties; therefore, instruction on reaction rates should be designed to emphasize a balanced integration of conceptual understanding and computational skills.